(untitled) (International Current Pharmaceutical Journal, 2015)
Cocoa powder and chocolate is most abundant flavonoids-plant product. Type 2 diabetes mellitus (T2DM) is health and epidemically serious metabolic disorder. The treatment and moreover preventing of T2DM is therapeutic target worldwide. This review focuses on antidiabetic mechanisms of cocoa products. Particularly, intensifying insulin sensitivity, which is a superior pathway for chronic glucose level control, and increasing insulin release for acute glucose level control. Accordingly, the hypoglycemic effect results in elevate synthesis and bioavailability of nitric oxide (NO). Subsequently, improve blood flow and capillary recruitment. DOI: http://dx.doi.org/10.3329/icpj.v4i2.21485 International Current Pharmaceutical Journal, January 2015, 4(2): 362-366